The arterial embolization in kidney tumors: preliminary communication - Francia-Vogelsang, Enrique; Pereyra Bonasso, Jorge; Sarasúa, Alberto; Pereyra, Ricardo; Mendy Noriega, Fabián (Cirugía del Uruguay, 1977)
Four cases of hypervascularized nephrocarcinomas were treated for per cutem embolic occlusion through catheterization of ren,l artery, followed by nephrectomy in 3 cases. Indications, tollerance and possible variations of procedure are discussed. The opportunity most favourable far nephrectomy is considered, followed by description of histopathologicalfindings. When embolization is complete, involving the kidney, nephrectomy performed after a brief interval 'is markedly facilitated and may begin by primary ligature of renal vein, thus reducing to a minimun, the risk of intraoperatory neoplasic dissemination.